2021
DOI: 10.1111/jch.14311
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of psychiatric comorbidities and serotonergic or noradrenergic medication use on blood pressure using 24‐hour ambulatory blood pressure monitoring

Abstract: In this study, the authors aimed to assess both nighttime and daytime blood pressure (BP) variability using 24‐hour ambulatory BP monitoring (ABPM) in persons with and without psychiatric conditions and with or without selective serotonin reuptake inhibitors (SSRIs) or serotonin‐norepinephrine reuptake inhibitors (SNRIs) treatment. In this retrospective study, patients who underwent psychiatric evaluation and ABPM within 6 months of each other between January 1, 2012 and December 31, 2017 were identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This effect is clearly dependent on SERT function, as SERT knock-out mice are less prone to the chronic 5-HT-induced drop in blood pressure [134]. Interestingly, some clinical studies have shown that chronic inhibition of 5-HT reuptake by SERT inhibitors reduced the risk of a myocardial infarction [135], but an increase in blood pressure was recorded at night [136]. In this regard, in dogs, chronic oral treatment with fluoxetine does not affect mean arterial blood pressure (measured at diurnal time), but the capsaicin-induced trigeminal CGRP release (resulting in vasodilatation) is diminished at the craniovascular (external carotid) level [137]; this finding may help explain the mechanism of action of some SERT inhibitors to treat migraine.…”
Section: Perspectives and Some Future Directionsmentioning
confidence: 99%
“…This effect is clearly dependent on SERT function, as SERT knock-out mice are less prone to the chronic 5-HT-induced drop in blood pressure [134]. Interestingly, some clinical studies have shown that chronic inhibition of 5-HT reuptake by SERT inhibitors reduced the risk of a myocardial infarction [135], but an increase in blood pressure was recorded at night [136]. In this regard, in dogs, chronic oral treatment with fluoxetine does not affect mean arterial blood pressure (measured at diurnal time), but the capsaicin-induced trigeminal CGRP release (resulting in vasodilatation) is diminished at the craniovascular (external carotid) level [137]; this finding may help explain the mechanism of action of some SERT inhibitors to treat migraine.…”
Section: Perspectives and Some Future Directionsmentioning
confidence: 99%